أثر اخلاقيات المهنة على الأمان الوظيفي في القطاع البلدي ( أمانه منطقة عسير ): The impact of professional ethics on job security in the municipal sector (Asir Region Municipality) - سعد بن ناصر آل عزام; عبدالله مهدي الجالي (Journal of North African Economies, 2025)
The study aimed to know the variables represented by professional ethics and job security with the aim of identifying its availability in the organization that is the subject of the research and drawing their importance, relationship and impact between them. A questionnaire was prepared to measure the relationship and impact, and a sample of (54) employees was selected from the research community. These results are based on the (AMOS) program, and the results have been reached. Spreadsheets provide the profession in the direction that is kept in mind that provides the provision of an organizational culture. Your confidence in the existence of the ethics required to influence workers in the field of assistance and finance, which enhances job security.